2008
DOI: 10.1007/s10620-008-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Caffeic Acid Phenethyl Ester on Intestinal Ischemia-Reperfusion Injury

Abstract: The intestinal IR injury may be reversed by anti-inflammatory and antioxidant actions of the CAPE. However, 30 mg/kg CAPE treatment may be more efficient in preventing intestinal IR injury in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
4
24
1
Order By: Relevance
“…Some of them such as IL-12p40 and CD3 were targeted in human clinical trials [43,44]. Naturally occurring compounds proven to have antioxidant and anti-inflammatory effects such as resveratrol, caffeic acid phenethyl ester (CAPE) [45] and any other potential candidate drug or extract especially extracts of Atractylodes spp. and Poncirus trifoliate [46] can be used as adjuvant agent with new potential candidate molecules for IBD therapy.…”
Section: Current and Future Developmentsmentioning
confidence: 99%
“…Some of them such as IL-12p40 and CD3 were targeted in human clinical trials [43,44]. Naturally occurring compounds proven to have antioxidant and anti-inflammatory effects such as resveratrol, caffeic acid phenethyl ester (CAPE) [45] and any other potential candidate drug or extract especially extracts of Atractylodes spp. and Poncirus trifoliate [46] can be used as adjuvant agent with new potential candidate molecules for IBD therapy.…”
Section: Current and Future Developmentsmentioning
confidence: 99%
“…As a fi rst step, SOD detoxifi es the superoxide anion to hydrogen peroxide (35). The intestinal I/R injury was associated with dramatic increases in MDA level and MPO activity and decrease in SOD activity (31).…”
Section: Table 3 the Effects Of Exercise On Intestinal Tissue Injurymentioning
confidence: 99%
“…It was demonstrated that administration of caffeic acid reduced oxidative stress by increasing antioxidant activities and decreasing oxidant status and lipid peroxidation in the intestine of rats in an experimental model of necrotizing enterocolitis (Tayman et al, 2011). Administration of caffeic acid has been also shown to completely block both the production of ROS from activated neutrophils and the XO system (Ma et al, 2006;Yildiz et al, 2009) and to protect intestinal tissues from ROS-mediated oxidative stress and reduce lipid peroxidation (Ek et al, 2008;Koltuksuz et al, 1999). Treatment of rats orally with caffeic acid resulted in a significant decrease in iron nitrilotriacetate-induced xanthine oxidase, lipid peroxidation, cglutamyl transpeptidase, and H 2 O 2 and there was a dose dependent and significant recovery of renal glutathione content and antioxidant enzymes (Rehman & Sultana, 2011).…”
Section: Reactive Oxygen and Nitrogen Speciesmentioning
confidence: 99%